The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1982
DOI: 10.1002/bbpc.19820861006
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Stabilities of the IIB/VIA‐Compounds at High‐Temperature Equilibrium Conditions

Abstract: Equilibrium vaporization behaviour of twelve IIB/VIA‐compounds of the type MeX was studied by means of high‐temperature mass spectrometry. In all cases except HgTe the existence of stable MeX(g)‐molecules was established. Bond energies D0(MeXgas) were determined by the thermodynamic third‐law method and range as follows: ZnO(g) (280.1 kJ/mol)/ZnS(g) (224.8)/ZnSe(g) (170.8)/ZnTe(g) (117.7)/CdO(g) (230.3)/CdS(g) (208.5)/CdSe(g) (127.7)/CdTe(g) (100.1)/HgO(g) (221.1)/HgS(g) (217.3)/HgSe(g) (144.5). ‐ Comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
(2 reference statements)
2
21
3
Order By: Relevance
“…It is the primary objective of the present paper to carry out relativistically corrected high-level ab initio calculations for the monomeric HgE and dimeric (HgE) 2 (E = O, S, Se) species and to study their relative stabilities and bonding features. If the dimeric mercury chalcogenides happen to be considerably more stable than the monomeric species, the discrepancy between measured [7] and calculated dissociation energies for the monomeric species [9,10] can be explained as resulting from dimerization (or even polymerization) of monomeric species in the gas phase. This would be the basis for answering questions that emerge in connection with points 1) to 4) mentioned above.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…It is the primary objective of the present paper to carry out relativistically corrected high-level ab initio calculations for the monomeric HgE and dimeric (HgE) 2 (E = O, S, Se) species and to study their relative stabilities and bonding features. If the dimeric mercury chalcogenides happen to be considerably more stable than the monomeric species, the discrepancy between measured [7] and calculated dissociation energies for the monomeric species [9,10] can be explained as resulting from dimerization (or even polymerization) of monomeric species in the gas phase. This would be the basis for answering questions that emerge in connection with points 1) to 4) mentioned above.…”
mentioning
confidence: 93%
“…Originally, gaseous HgO was tentatively identified by infrared spectroscopy in rare gas matrices under nonstationary vaporization conditions. [6] Later, mass spectrometric measurements suggested [7] a dissociation energy D 0 of 53 AE 8 kcal mol À1 for HgO, which implied that the reaction of gaseous elemental mercury with bromine oxide should be nearly thermoneutral [D 0 (BrO) = 55.2 AE 0.4 kcal mol À1 as obtained from heats of formation at 0 K [8] ]. However, recent high-level ab initio calculations predict for the dissociation energy D e of HgO a 50 kcal mol À1 lower value of just 4 kcal mol À1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[59] Filatov and Cremer [19] have suggested that the mass-spectrometric investigation of HgE molecules [65] were flawed by the fact that mixtures of HgE dimers and trimers were measured. Such an error is unlikely under normal conditions, because the natural distribution of Hg and E isotopes should lead to m/e signals clearly different for monomer, dimer, and trimer.…”
mentioning
confidence: 99%